PENGEMBANGAN APLIKASI SISTEM INFORMASI GEOGRAFIS UNTUK MONITORING GEMPABUMI - Irwansyah, Edy; Saputra, Tri Buana; Piu, Lim; Wirangga, Krisna (Institute of Research and Community Outreach - Petra Christian University, 2012)
This Research conducted to develop geographic information system (GIS) that can be used to manage data and visualize the earthquake information. The research methodology consisted of collecting spatial data and non spatial data and system design. System design consists of designing the flow of data, designing databases, designing menus and design screens. The conclusion that can be drawn from this study is that GIS is developed to display information about how the earthquake that has been and is happening with magnitude parameters in a visual form suitable conditions. GIS is designed to use its own database and have the capacity to perform spatial data processing and non-spatial to generate a tsunami early warning system. This system can also simplify and accelerate the delivery of earthquake information to the public.